2021
DOI: 10.1063/5.0027885
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN/GaN metal–insulator–semiconductor high electron mobility transistors (MISHEMTs) using plasma deposited BN as gate dielectric

Abstract: AlGaN/GaN metal–insulator–semiconductor high electron mobility transistors (MISHEMTs) were fabricated on Si substrates with a 10 nm boron nitride (BN) layer as a gate dielectric deposited by electron cyclotron resonance microwave plasma chemical vapor deposition. The material characterization of the BN/GaN interface was investigated by X-ray photoelectric spectroscopy (XPS) and UV photoelectron spectroscopy. The BN bandgap from the B1s XPS energy loss is ∼5 eV consistent with sp2 bonding. The MISHEMTs exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The fabricated AlGaN/GaN HEMT with h-BN showed a very promising performance, including a cutoff frequency (f T ) and maximum oscillation frequency (f MAX ) as high as 28 and 88 GHz, respectively, enabled by an effective passivation of surface defects on the HEMT wafer to deliver accurate information with minimized power loss. Tsung-Han Yang et al [54] prepared the AlGaN/GaN MIS-HEMTs with electron cyclotron-resonance microwave plasma chemical-vapor-deposition (ECR-MPCVD), depositing BN as a gate dielectric. The h-BN could effectively reduce the leakage current and improve device performance.…”
Section: The Passivation Of H-bnmentioning
confidence: 99%
“…The fabricated AlGaN/GaN HEMT with h-BN showed a very promising performance, including a cutoff frequency (f T ) and maximum oscillation frequency (f MAX ) as high as 28 and 88 GHz, respectively, enabled by an effective passivation of surface defects on the HEMT wafer to deliver accurate information with minimized power loss. Tsung-Han Yang et al [54] prepared the AlGaN/GaN MIS-HEMTs with electron cyclotron-resonance microwave plasma chemical-vapor-deposition (ECR-MPCVD), depositing BN as a gate dielectric. The h-BN could effectively reduce the leakage current and improve device performance.…”
Section: The Passivation Of H-bnmentioning
confidence: 99%
“…It can be found that the interface of h-BN/β-Ga 2 O 3 is much more smooth and abrupt than that of SiO 2 /β-Ga 2 O 3 (as shown in the white rectangles in the picture). Therefore, we can conclude that the improved electrical properties of Ta-doped β-Ga 2 O 3 MISFET with h-BN gate dielectric are due to the smaller surface roughness, good insulating properties of the h-BN gate dielectric, and low defect density at the h-BN/β-Ga 2 O 3 interface …”
mentioning
confidence: 91%
“…Figure 3b shows the output characteristics of the β-Ga 2 O 3 MISFET with h-BN gate dielectric. The much smaller R on of 12.5 Ω•mm and R on,sp of 6.3 mΩ•cm 2 were realized for the h-BN/β-Ga 2 O 3 MISFET, which are characterized using the same method 18 Besides, the energy-band structure of the h-BN/β-Ga 2 O 3 heterostructure was further studied. Figure 4a shows the ultraviolet photoelectron spectroscopy (UPS) spectra of the Ta-doped β-Ga 2 O 3 , from which the corresponding work function and valence band maximum of the Ta-doped β-Ga 2 O 3 are calculated to be ∼4.25 and 10.12 eV, respectively.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…and BN [18]. Various deposition techniques were used to form these insulating gate dielectrics, such as plasma-enhanced chemical vapor deposition (PECVD), low-pressure chemical vapor deposition (LPCVD), in situ metal-organic chemical vapor deposition (MOCVD), and so on [19,20].…”
Section: Introductionmentioning
confidence: 99%